Constraining the NuMI neutrino flux using inverse muon decay reactions in MINERvA - Ruterbories, D.; Ahmad Dar, Z.; Akbar, F.; Ascencio-Sosa, M.V.; Bashyal, A.; Bercellie, A.; Betancourt, M.; Bodek, A.; Bonilla, J.L.; Bravar, A.; Budd, H.; Caceres, G.; et al. (American Physical Society, 2021)
Inverse muon decay, νμe¯ → μ¯νₑ, is a reaction whose cross section can be predicted with very small uncertainties. It has a neutrino energy threshold of ≈11 GeV and can be used to constrain the high-energy part of the flux in the NuMI neutrino beam. This reaction is the dominant source of events which only contain high-energy muons nearly parallel to the direction of the neutrino beam.We have isolated a sample of hundreds of such events in neutrino and antineutrino enhanced beams, and have constrained the predicted high-energy flux.
Keywords: Neutrino; Physics; Muon; Muon neutrino; Nuclear physics; Flux (metallurgy); Particle physics; Inverse; Neutrino detector; Neutrino oscillation; Chemistry; https://purl.org/pe-repo/ocde/ford#1.03.03